2018
DOI: 10.11114/jets.v6i3a.3157
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Grit Levels of Teachers According to Personal Variables

Abstract: The purpose of this study is to determine whether or not the grit level of teachers varied according to their personal variables. The research, in the descriptive screening model, was conducted on 360 teachers who were chosen according to simple random sampling method and working in primary schools, secondary schools and high schools in Adapazarı district of Sakarya province. In the data collecting phase, “Grit Scale”, which is developed by Duckworth and Quinn (2009a) and adapted into Turkish culture by Argon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
3
12
0
4
Order By: Relevance
“…The findings of the current study confirmed those of the later studies. The current study partly confirmed the findings of a recent study with Turkish in-service teachers in which female teachers hold significantly higher perseverance of effort and similar consistencies of interest than males (Argon & Kaya, 2018). Since pre-service teachers in Turkey consist of an overwhelming number of females, the current study has a disproportionate number of females than males.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of the current study confirmed those of the later studies. The current study partly confirmed the findings of a recent study with Turkish in-service teachers in which female teachers hold significantly higher perseverance of effort and similar consistencies of interest than males (Argon & Kaya, 2018). Since pre-service teachers in Turkey consist of an overwhelming number of females, the current study has a disproportionate number of females than males.…”
Section: Discussionsupporting
confidence: 89%
“…Teachers' self-efficacy inspires teachers to maintain their perseverance and invest their time, emotions, passions and energy to reach success, and find the obstacles that hinder their success. So, the more diligent and hard-working teachers are, the more efficacious they are in recovering from setbacks and remaining in their jobs (Argon & Kaya, 2018). It is worth mentioning that teachers' beliefs and efficacy do not sustain over time and teachers, therefore, need workshops, practice, perseverance, and effort to develop their professional development (Chen, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Teacher grit has been characterized as teachers' possession of durability, domination, fearlessness, forbearance, constancy, and confidence. For example, the durability of instructors depends upon their impetus, endeavor, and perseverance to enable them to reach their goals in their profession (Argon & Kaya, 2018). Besides, Bobek (2002) defined teacher grit as having the aptitude to adapt to diverse teaching conditions and face up to adverse conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Elde edilen bulgular öğretmenlerin yüksek düzeyli bir dayanıklılık sergilediklerini göstermiştir. Söz konusu bulgu alanyazın ile tutarlılık sergilemektedir (Argon ve Kaya, 2018;Botou vd., 2017;Bowles ve Arnup, 2016;Brouskeli vd., 2018;Çalışkan, 2011;Li vd., 2019;Peixoto vd., 2020;Pretsch vd., 2012;Razmjoo ve Ayoobiyan, 2019). Araştırma verilerinin COVID-19 sürecinde toplandığı göz önünde bulundurulduğunda elde edilen bulgunun oldukça önemli olduğu ifade edilebilir.…”
Section: Discussionunclassified